1986
DOI: 10.1002/eji.1830160309
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of thymocyte proliferation and survival by deoxynucleosides. Deoxycytidine produced by thymic accessory cells protects thymocytes from deoxyguanosine toxicity and stimulates their spontaneous proliferation

Abstract: Deoxyguanosine (dGuo) inhibits thymic blast DNA synthesis and then induces thymocyte cell death. The dGuo inhibitory action, measured with four different assays (spontaneous thymidine incorporation, immunofluorescent detection of 5-bromodeoxyuridine incorporation, dye exclusion, tetrazolium salt cleavage), was suppressed in the presence of supernatants from cultures containing phagocytic cells. In particular, we studied the anti-dGuo activity in supernatants from thymic reticulum cultures (TRS) and in those fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 22 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Due to endogenous thymidine competition [26], BrdUrd is not reutilized in the thymus and can thus be used for precursor product studies which were not possible with tritiated thymidine. We have already used this method to study thymocyte dynamics and differentiation in the normal and regenerating murine thymus [27-301.…”
Section: [I 67531mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to endogenous thymidine competition [26], BrdUrd is not reutilized in the thymus and can thus be used for precursor product studies which were not possible with tritiated thymidine. We have already used this method to study thymocyte dynamics and differentiation in the normal and regenerating murine thymus [27-301.…”
Section: [I 67531mentioning
confidence: 99%
“…The recent development of anti-bromodeoxyuridine (BrdUrd) antibodies [24,251 gives the opportunity to study the proliferative kinetics of cells in relation to their surface phenotype. Due to endogenous thymidine competition [26], BrdUrd is not reutilized in the thymus and can thus be used for precursor product studies which were not possible with tritiated thymidine. We have already used this method to study thymocyte dynamics and differentiation in the normal and regenerating murine thymus [27-301. We have shown that the main thymocyte differentiation pathway in vivo is DN + double-positive (DP)-+ single-positive (SP) cells, making CD4' 8' DP cells an important intermediary stage, and not a pure dead end, despite the death of the majority of DP cells in the cortex, The DN+ DP transition happens in cycling cells [30].…”
Section: [I 67531mentioning
confidence: 99%
“…Thymic epithelial cells (TEC) are believed to play an important role in the process by which immature lymphoid cells differentiate into immunocomponent T cells in the thymus [1][2][3][4]. TEC have been shown to express antigen-presenting activity, and it has been suggested that immature T cells interact with self Ag presented by TEC during their maturation process, and are educated to distinguish self Ag from nonself Ag through this interaction [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the dose used in our study corresponds to 153 mg/kg in the human. In fact, doses of dC have been used to antagonize the toxicity of gemcitabine and ara-C (42,43), thymidine (44), and deoxyguanosine (45), which would be sufficient for generating detectable CEST MRI contrast. Although the exact dC concentrations in the plasma or tissues were not measured in these studies, we still speculate that a mmol/L concentration level of dCTP is achievable based on previously reported values of gemcitabine.…”
Section: Discussionmentioning
confidence: 99%